Relationship between Self-Confidence and Teaching Anxiety and Pre-Service Teachers’ Perceptions of their Teaching Skills - Dwi Lestari; Oki Uliasari; Mutiea Dwi Artika Sari; Netriwati Netriwati; Fadly Nendra (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mastery of subject matter is not the only factor in pre-service teachers’ views of their instructional abilities. Psychological factors, including self-confidence and teaching anxiety are also presumed to be associated with perceived teaching skills, particularly in microteaching activities. So, this study aimed to look at how self-confidence, teaching anxiety, and pre-service teachers' views on their own teaching abilities are connected. This study used a quantitative method and followed a correlational research design. The group included 60 future teachers from Raden Intan State Islamic University in Lampung who had finished the microteaching course and were chosen through purposeful sampling. Data was gathered using questionnaires with a Likert scale, which had already been checked to make sure they were valid and reliable. The tests to check if the questionnaire questions were valid and reliable showed that all the items were both valid and reliable, with Cronbach’s Alpha scores of 0.907, 0.949, and 0.979. The data were checked for normality, and then a Spearman’s rank correlation was used to analyze the relationships because the data did not follow a normal distribution. The results showed that there was not a strong connection between self-confidence and how people see their teaching skills (rₛ = 0.033, p = 0.804), and also no strong link between teaching anxiety and how people see their teaching skills (rₛ = −0.203, p = 0.121). Also, there wasn't a strong connection between self-confidence and teaching anxiety (rₛ = −0.210, p = 0.106). The correlation coefficients showed that the connections between the variables were either very weak or weak, and some were positive while others were negative. This study is new because it shows that self-confidence and teaching anxiety are not the main things that affect how pre-service teachers see their own teaching abilities. The findings indicate that having real teaching experience, knowing the subject well, and being prepared to teach are the main factors that influence how people see teaching abilities. So, this study shows that improving the quality of future teachers should not just focus on their mental health but also on building their teaching skills and giving them more real classroom experience.